Gastronomi Pariwisata dan Motivasi Pariwisata: Rumah Produksi Tahu Susu Lembang - Dina Fitriani; Sifa Sukowati; Asep Parantika (Jurnal Ilmiah Wahana Pendidikan, 2023)
Gastronomy tourism is an important consideration among tourists when choosing a tourist destination.. The main objective of the study was to measure the level of satisfaction in the tourists and further consider the craftsmanship of creation as a component of motivational tourism visitor. This type of research is qualitative research. The population of this study was visitors or tourists who came to the Rumah Produksi Tahu Susu Lembang with a sample of 30 tourists. Data is collected by interviewing travellers at the destination. Gastronomic motivation has an impact on tourism locations and according to research, gastronomic experiences affect tourist satisfaction